Model of Customer Loyalty in the Electric Word of Mouth, Celebrity Endorser and Payment System with Trust as Mediation Variable - Hasibuan, Ahmad Nurdin; Limakrisna, Nandan; Moeins, Anoesyirwan (Siber International Journal of Digital Business (SIJDB), 2023)
Technological advances have significantly changed the way consumers interact with digital. Electronic word of mouth communication, facilitated through social media platforms and online review sites, has become a powerful tool for consumers to share their opinions and experiences. This digital era is also in business making the most of electronic communication, namely word of mouth (eWOM) and celebrity endorsers to attract and retain customers. Also, with the growing popularity of various payment systems, understanding their impact on customer loyalty is critical. This study aims to investigate the relationship between eWOM, celebrity endorsers, payment systems, trust, and customer loyalty. Trust will be examined as a mediating variable that can help explain the process by which eWOM, celebrity endorsements and payment systems influence customer loyalty. This study aims to investigate the relationship between eWOM, celebrity endorsements, payment systems, trust, and customer loyalty. Specifically, this study will explore whether trust mediates the effects of eWOM, celebrity endorsements, and payment systems on customer loyalty in the context of digital markets. The literature review will investigate existing research on customer loyalty, eWOM, celebrity endorsements, payment systems, and trust. It will highlight relevant theory and empirical findings related to these variables and identify potential gaps that this study seeks to address. The theory used in this study is the Technology Acceptance Model (TAM) theory which was developed by Fred Davis in 1986 to explain the acceptance and adoption of information technology by individuals. This model focuses on user behavior in accepting or rejecting new technology, especially in the context of information systems and computer technology. Theory of Planned Behavior (Theory of Planned Behavior/TPB) is a social psychological theory used to explain and predict human behavior. This theory was developed by Martin Fishbein and Icek Ajzen in 1980 as an extension of the Theory of Reasoned Action (TRA). Intention-Based Behavior Theory (Theory of Reasoned Action/TRA) is a social psychological theory developed by Martin Fishbein and Icek Ajzen in 1967. TRA aims to explain and predict human behavior based on consumer behavioral intentions.